1999
DOI: 10.1007/pl00012368
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of Body Fluid Disturbances in Patients with Obstructive Jaundice

Abstract: Postoperative renal dysfunction in obstructive jaundice (OJ) patients has been associated with hypovolemia and depletion of the extracellular water compartment (ECW). The aim of the study was to evaluate the preoperative status of body compartments in OJ patients measured by two methods. In a prospective study 39 OJ patients (11 benign and 28 malignant obstructions) were investigated, with 15 healthy subjects used as a control group (CG). Bioelectrical impedance analysis (BIA) determinations and values derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
4
18
0
2
Order By: Relevance
“…Our study found a drop in sodium excretion, and the concentration of sodium in urine that was related to the increase in aldosterone concentration, which suggests a rise in sodium retention in the distal tubule. In this respect, results corroborate clinical studies run by our group, which showed that patients with OJ suffered a depletion of extracellular volume that is directly related to biliary obstruction (16), and had renin and aldosterone levels in the upper range of normality (5). ET-1 is a peptide with a powerful vasoconstrictor action that is involved in the genesis of several diseases, mainly in the hepato-biliary area.…”
Section: Discussionsupporting
confidence: 88%
“…Our study found a drop in sodium excretion, and the concentration of sodium in urine that was related to the increase in aldosterone concentration, which suggests a rise in sodium retention in the distal tubule. In this respect, results corroborate clinical studies run by our group, which showed that patients with OJ suffered a depletion of extracellular volume that is directly related to biliary obstruction (16), and had renin and aldosterone levels in the upper range of normality (5). ET-1 is a peptide with a powerful vasoconstrictor action that is involved in the genesis of several diseases, mainly in the hepato-biliary area.…”
Section: Discussionsupporting
confidence: 88%
“…In our in vivo experiments, increased LVSEP, +dP/dt max and -dP/dt max , were associated with myocardial contractility, suggesting up regulation of the sympathetic nervous system. In addition, LVEDP which directly relates to the cardiac preload might remain unchanged possibly not owing to the depletion of body fluid in obstructive jaundice [30,31]. However, the lower heart rate may be caused in part by accumulated bile acids, which impair cardiac function by affecting calcium uptake from the sarcoplasmic reticulum [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the glomerular filtration rate and acute renal failure (ARF) are observed in 60-75 and 4-18% of the patients respectively. The mortality of patients with renal failure varies between 32 and 100% [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%